Diagnosis of Ia-Ic stages of serous high-grade ovarian cancerby the lipid profile of blood serum - Mariia V. Iurova; Vladimir E. Frankevich; Stanislav V. Pavlovich; Vitali V. Chagovets; Nataliya L. Starodubtseva; Grigory N. Khabas; Lev A. Ashrafyan; Gennady T. Sukhikh (IP Berlin A.V., 2021)
Background. Ovarian cancer is the first fatal malignancy of the female reproductive system. Early detection is associated with better outcomes, but is significantly difficult because of asymptomatic or low-symptomatic course. Aim. To study the possibility of detecting of OC in early stages (IaIc) by the lipid profile of blood serum obtained using high-performance liquid chromatography with mass spectrometric (MS) detection. Materials and methods. An observational "case-control" study was conducted in period November 2019 July 2020 in the Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology. 41 patients were included: group 1 (main) 28 patients with histologically verified high grade serous ovarian cancer of IIV FIGO stage, group 2 (control) 13 conditionally healthy women. Venous blood samples were collected immediately before the operation. Extracts of serum lipids were obtained in accordance with the modified Folch method. The composition of the samples was analyzed by electrospray ionization MS. Using the method of discriminant analysis and orthogonal projections to latent structures (OPLS-DA) were building OPLS-models based on profile of significant lipids. The comparison based on the non-parametric MannWhitney test. Results. The presence of 128 lipids in blood serum samples makes a major contribution to the OPLS-models, that are different for patients with IIV OC stage and controls. The OPLS-model parameters are: R2=0.87 and Q2=0.80, the area under the ROC curve reached 1, sensitivity and specificity of the model 100%. The second OPLS-model was developed to assign patients to 13 blood serum samples of the control group or to 5 blood samples of patients with I-II stages of OC: 108 lipids made the main contribution to this model (R2=0.97, Q2=0.86). The third OPLS-model was constructed to distinguish patients with earlier (IaIa stages; n=5) and advanced (IIaIVa; n=23) stages: R2=0.96 and Q2=1.00, AUC=0.99. Diglycerides, triglycerides, phosphatidylcholines, ethanolamines, sphingomyelins, ceramides, phosphatidylserines, phosphoinositols and prostaglandins significantly differ in the blood serum samples of patients with IaIc stages of OC and patients with IIIV stages and controls, that indicates the diagnostic value. Conclusion. It is possible to distinguish a healthy person from patient with IaIc or IIIV stages of OC. Serum oncolipids profile obtained by high-performance liquid chromatography with MS detection can be used as markers of early stages of OC, that are associated with better prognosis.